2020
DOI: 10.1186/s12909-020-02265-4
|View full text |Cite
|
Sign up to set email alerts
|

A multi-method exploratory study of health professional students’ experiences with compliance behaviours

Abstract: Background Research in healthcare, including students as participants, has begun to document experiences with negative compliance, specifically conformity and obedience. There is a growing body of experimental and survey literature, however, currently lacking is a direct measure of the frequency at which health professional students have negative experiences with conformity and obedience integrated with psychological factors, the outcomes of negative compliance, and students’ perceptions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…Previous research indicates anywhere between 50% -95% of students will demonstrate conformity or obedience in a situation that can result in patient harm. 1,3,[27][28][29][33][34][35][36][37] However, based on the results of our study, overall, students believe themselves to be less susceptible to conformity and obedience than peers. Informing students, instructors, and practitioners about the BTAE can potentially increase awareness of personal susceptibility to compliance behaviour and that their own behaviour, knowledge, and skills will likely not be as good as expected.…”
Section: Expected Behaviourmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous research indicates anywhere between 50% -95% of students will demonstrate conformity or obedience in a situation that can result in patient harm. 1,3,[27][28][29][33][34][35][36][37] However, based on the results of our study, overall, students believe themselves to be less susceptible to conformity and obedience than peers. Informing students, instructors, and practitioners about the BTAE can potentially increase awareness of personal susceptibility to compliance behaviour and that their own behaviour, knowledge, and skills will likely not be as good as expected.…”
Section: Expected Behaviourmentioning
confidence: 96%
“…The vignettes reflect previous studies that demonstrated conformity and obedience in health professions students and practitioners. [26][27][28][29][30] The vignettes were tested and modified using cognitive interviews, 31 a process of questioning for understanding responses process and content to identify sources of confusion in assessment, conducted with practitioners and students from health professions [3], psychology [2], educational psychology [1], and business [1] (for the vignettes with response scales, please see the supplemental material).…”
Section: Study Design and Samplingmentioning
confidence: 99%
See 3 more Smart Citations